Agricultural and Natural Resources Policies in Nepal: A Review of Formulation and Implementation Processes and Issues - Joshi, Ganesh R.; Joshi, Binaya (Nepal Public Policy Review, 2021)
The government of Nepal has made efforts to formulate and implement the agricultural sector policies since the 1960s. It has formulated dozens of policies and strategies in agriculture, forestry, agro-forestry, climate change, land use, poverty alleviation, irrigation, etc. Some of the policies seem to be targeted to specific groups and communities (poverty alleviation policy), to different sectors and commodities (forest, agriculture, poultry, coffee, etc.), and address international and national concerns and priorities (climate change policy, agrobiodiversity). This study aims to review the implementation of the policy provisions of major agricultural and natural resources policies, explore possible causes for it and suggest measures to effectively implement policy provisions in the future. We have reviewed seven agriculture policies for their provision and implementation and identified some common features and inadequacies. Our recommendations for policy reform include the practice of wider consideration, inter-policy coherence, sufficient institutional framework, periodic policy evaluation, improved accountability, and consideration for national Interest.